Persepsi Mahasiswa Terhadap Faktor-Faktor Yang Mempengaruhi Sistem Pendidikan Nasional Indonesia (Studi Kasus di Prodi S1 Bahasa dan Sastra Inggris Unsoed - Syaifur Rochman (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2013)
Abstract: This article discusses a survey in S1 Studies English Language and Literature Unsoed about students’ perceptions of the factors that influence the national education system in Indonesia. There are 7 respondents in the survey consisted of 5 women and 2 men. They were respondents as doing research for a thesis under the guidance of the author deals with international standard junior high school in Purwokerto. Data were collected between 2009 and 2011 through in-depth discussion to find out their views on the national education system. The results showed that most respondents have similar views about the national education system in Indonesia.